Evaluation of periodontal status and detection of Dialister pneumosintes in cerebral palsy individuals: A Case-Control study - S Riyaz Mohammed; Nithya Anand; S C Chandrasekaran; Krishnan Mahalakshmi; Kesavaram Padmavathy (Wolters Kluwer Medknow Publications, 2018)
Background: The worldwide prevalence of cerebral palsy among live births is estimated to be between 1.9 and 3.6/1000. The presence of periodontal disease in cerebral palsy children typically is due to bacterial plaque accumulation caused by their inability to correctly clean their own teeth, difficulties in chewing and swallowing food, and improper movements of masticatory muscles and tongue muscles. Objectives: The objective of this study is to estimate the periodontal status in cerebral palsy individuals and evaluate the presence of Dialister pneumosintes. Materials and Methods: Thirty cerebral palsy children from the Spastics Society of Tamilnadu with signs of periodontitis were compared with the same number of age- and gender-matched controls for oral hygiene and periodontal parameters. Subgingival plaque samples were screened for the presence of respiratory pathogen D. pneumosintes by polymerase chain reaction (PCR). Results: A variation was noted between types of cerebral palsy individuals with a mean probing pocket depth value of 6 in spastic type, 4.86 in the ataxic, and 4.3 in the dyskinetic. Clinical attachment level varied from 6.71 in spastic to 5.43 in ataxic and 3.50 in dyskinetic. Oral hygiene index-simplified ranged from 2.764 in spastic to 2.25 in ataxic and 1.41 in dyskinetic. PCR results indicated 25% and 21.7% positivity for D. pneumosintes among cerebral palsy and control group, respectively. The odds ratio calculated to estimate the risk of periodontitis due to D. pneumosintes was 0.765. Conclusion: It was concluded that oral hygiene status and severity of periodontitis worsens as the rigidity and muscle tone limiting limb movement increases in cerebral palsy individuals.